“Impact Of Social Media On Digital Society” (Journal of Namibian Studies : History Politics Culture, 2023)
The rapid proliferation of social media platforms has led to a profound transformation of modern society, ushering in the era of the digital age. This paper examines the multifaceted impact of social media on various dimensions of digital society. Through an interdisciplinary lens, encompassing fields such as sociology, psychology, communication studies, and technology, we explore how social media has influenced communication patterns, social interactions, information dissemination, personal identities, and societal structures. The paper delves into the positive aspects of social media, including its role in fostering global connectivity, enabling information sharing, and empowering marginalized voices. Additionally, it scrutinizes the negative consequences, such as the spread of misinformation, erosion of privacy, and the emergence of online echo chambers that reinforce societal polarization. The dynamics of social comparison, and the psychological implications of curated online personas are also discussed in the context of individual well-being.